Construction Hydrophobized Based on Silicon-Organic Compounds and Its Comparative Analysis (Global Scientific Review, 2023)
The article presents the synthesis of an organosilicon water repellent based on vinylethynylmagnesium bromide for building materials. The reduction in water absorption as a result of the influence of a water repellent on the material is also scientifically substantiated. A comparative analysis of the synthesized water repellent with existing water repellents is described